The determinants of self-rated health in the Republic of Ireland: Further evidence and future directions - Liam Delaney; Colm Harmon; Cecily Kelleher; Caroline Kenny (University College Dublin, UCD School of Economics, 2008)
This paper examines the determinants of self-rated health in the Republic of Ireland using data from the 2001 Quarterly National Household Survey Health Module and the 2005 ESRI Time Usage Survey. Results indicate that self-rated health is a useful proxy for self-reported chronic illness indices. Higher education, having private medical insurance cover and being married is associated with better self-rated health. The strong inverse relationship between age and self-rated health is found to be robust to the inclusion of self-reported morbidity. Caregivers display lower self-rated health, even after controlling for age, marital status and education. We find only minor effects of gender. Understanding further the causal nature of the above associations is a key issue for future research.
hdl:10197/967
Keywords: 330